Industrial Relationship Between Worker, Entrepreneur and Government On the Outsourcing Program in PT. Aru Raharja Indonesia - Anandha budiantoro; Ma'ruf Akbar; Wibowo (IJHCM (International Journal of Human Capital Management), 2019)
This study aims to determine whether the Industrial Relationship Between Worker, Entrepreneur and Government at PT. Aru Raharja Indonesia has achieved its goal. This research method used an evaluative descriptive method. The object of the research was focused on the Industrial relationship between worker, entrepreneur and government On the outsourcing program of PT. Aru Raharja Indonesia Data is collected through observatied, documentation studied, and indepth interview. Data analysis used descriptive evaluative techniques, through four stages, namely: data collection, data reduction, data display and conclusion drawing/verification. The results of the studied found that industrial relationship at the outsourcing program of PT. Aru Raharja Indonesia is classified as moderate. This indicates that the industrial relation to the outsourcing program of PT. Aru Raharja Indonesia still needs to be repaired in its implementation. It can be less effective in the process of communication between worker, entrepreneur and government in the form of coaching, supervision and coordination between the parties involved in the relationship industry